Software tools for project management: focus on collaborative management - Ferreira, Maria Ester Pereira (2014)
Today, projects involve members from different geographical areas more than any other time in history. Thus, adequate Collaborative Project Management Software (CollabPMS) solutions are needed to enable individuals and organizations to manage, communicate and work together across time and space barriers. This article describes a set of managerial and collaborative functionalities that a CollabPMS should provide to support the complexities of a distributed project effectively. Out of hundreds software packages available in the market, four were selected, ProjectLibre, Redmine, Microsoft Project 2013 and Clarizen, to assess if they have the described functionalities. Clarizen can be considered the best software for managing distributed projects, because it provides, by default, all the managerial functions and the collaborative features that support the coordinated collaboration level. ProjectLibre was the software that less stood out in this evaluation, although it provides the majority of the outlined managerial functionalities it doesn't support any level of collaboration.